EFFECT OF GALAM LEAF EXTRACT AND TRI-CALCIUM SILICATE CEMENT ON NEUTROPHIL CELLS IN WISTAR RAT PULP - Fedriko Gamaliel Putra; Sherli Diana; Nurdiana Dewi; Yusrinie Wasiaturrahmah; Amy Nindia Carabelly (Dentino: Jurnal Kedokteran Gigi, 2024)
Background: Pulp capping is a method of sealing the pulp chamber in teeth with cavities that extend to the pulp. Direct pulp capping involves applying a material directly onto the exposed pulp tissue. Tri-calcium silicate cement (Ca3SiO5) is commonly used due to its nanoparticle mineral composition, but it can cause continued inflammation. Galam leaf (Melaleuca cajuputi) is known for its anti-inflammatory properties, owing to secondary metabolites like alkaloids, flavonoids, polyphenols, and saponins, potentially compensating for the drawbacks of tri-calcium silicate cement. Purpose: To determine the effect of combining Galam leaf extract (Melaleuca cajuputi subsp. Cumingiana (Turz) Barlow) with tri-calcium silicate cement as a direct pulp capping material on neutrophil cell count in the pulp of Wistar rats (Rattus norvegicus). Methods: This pure experimental study used a posttest-only control design. Thirty-six Wistar rats were divided into nine groups: one received a combination of 100% Galam leaf extract and tri-calcium silicate cement; one positive control group received tri-calcium silicate cement alone; and one negative control group received direct placement with glass ionomer cement (GIC). The neutrophil cell count was assessed on days 1, 2, and 3. Results: Two-way ANOVA results indicated a significant effect based on treatment and time (p < 0.05). Further analysis with the Post Hoc Bonferroni test (p < 0.05) revealed differences in neutrophil cell counts across nearly all groups on days 1, 2, and 3. Conclusion: The combination of 100% Galam leaf extract and tri-calcium silicate cement significantly reduced neutrophil cell counts compared to both positive and negative control groups on days 1, 2, and 3, indicating anti-inflammatory effect.